How well do ordinary Americans forecast the growth of COVID-19? - Fansher, Madison; Adkins, Tyler J.; Lewis, Richard L.; Boduroglu, Aysecan; Lalwani, Poortata; Quirk, Madelyn; Shah, Priti; Jonides, John (Memory & Cognition, 2022)
Across three experiments (N = 1565), we investigated how forecasts about the spread of COVID 19 are impacted by data trends, and whether patterns of misestimation predict adherence to social-distancing guidelines. We also investigated how mode of data presentation influences forecasting of future cases by showing participants data on the number of COVID-19 cases from a 5-week period in either graphical, tabular, or text-only form. We consistently found that people shown tables produced more accurate forecasts compared to people shown line-graphs of the same data; yet people shown line-graphs were more confident in their estimates. These findings suggest that graphs engender false-confidence in the accuracy of forecasts, that people's forecasts of future cases have important implications for their attitudes concerning social distancing, and that tables may be better than graphs for informing the public about the trajectory of COVID-19.